2003
DOI: 10.1038/nature01477
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond radio bursts from strong plasma turbulence in the Crab pulsar

Abstract: The Crab pulsar was discovered by the occasional exceptionally bright radio pulses it emits, subsequently dubbed 'giant' pulses. Only two other pulsars are known to emit giant pulses. There is no satisfactory explanation for the occurrence of giant pulses, nor is there a complete theory of the pulsar emission mechanism in general. Competing models for the radio emission mechanism can be distinguished by the temporal structure of their coherent emission. Here we report the discovery of isolated, highly polarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
390
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(411 citation statements)
references
References 25 publications
18
390
1
2
Order By: Relevance
“…Observations by Hankins et al (2003) revealed that giant pulses at 5.5 GHz contain nanosecond wide subpulses and the presence of such narrow features has been predicted in numerical modelling by Weatherall (1998). At these frequencies the radio emission character of the Crab pulsar changes, with the interpulse emission becoming dominant.…”
Section: Introductionmentioning
confidence: 83%
“…Observations by Hankins et al (2003) revealed that giant pulses at 5.5 GHz contain nanosecond wide subpulses and the presence of such narrow features has been predicted in numerical modelling by Weatherall (1998). At these frequencies the radio emission character of the Crab pulsar changes, with the interpulse emission becoming dominant.…”
Section: Introductionmentioning
confidence: 83%
“…In reality, however, pulsars have been shown to exhibit variability in their emission over every timescale which they can be observed (i.e. from nanosecond bursts to multi-decadal variations; see, e.g., Hankins et al 2003;Keane 2013;Lyne et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The width of this GP is τ ≤ 15 ns (Soglasnov et al 2004). Hankins et al (2003) found in pulsar PSR B0531+21 the pulse structure as short as 2 ns. If one interprets this pulse duration in terms of the maximum possible size of emitting region l ≤ c × τ , where c is the speed of a light, the time-scale τ =2 ns corresponds to a light-travel size of an emitting body l of only 60 cm, the smallest object ever detected outside our solar system.…”
Section: Observationsmentioning
confidence: 89%